End of the megafauna : the fate of the world's hugest, fiercest, and strangest animals - MacPhee, R. D. E.; Schouten, Peter (New York ; London : W.W. Norton & Company, Inc., 2019)
"The fascinating lives and puzzling demise of some of the largest animals on earth. Until a few thousand years ago, creatures that could have been from a sci-fi thriller--including gorilla-sized lemurs, 800-pound birds, crocodiles that weighed a ton or more--roamed the earth. These great beasts, or "megafauna," lived on every habitable continent and on many islands. With a handful of exceptions, all are now gone. What caused the disappearance of these prehistoric behemoths? No one event can be pinpointed as a specific cause, but several factors may have played a role. Paleomammologist Ross D.E. MacPhee explores them all, examining the leading extinction theories, weighing the evidence, and presenting his own conclusions. He shows how theories of human overhunting and catastrophic climate change fail to account for critical features of these extinctions, and how new thinking is needed to elucidate these mysterious losses. Along the way, we learn how time is determined in earth history; how DNA is used to explain the genomics and phylogenetic history of megafauna--and how synthetic biology and genetic engineering may be able to reintroduce these giants of the past. Until then, gorgeous four-color illustrations by Peter Schouten re-create these megabeasts here in vivid detail."--
Preface : Lost in near time -- Big -- "This sudden dying out" -- The world before us -- The hominin diaspora -- Explaining near time extinctions : first attempts -- Paul Martin and the planet of doom : overkill ascendant -- Action and reaction -- Overkill now -- Where are the bodies, and other objections to overkill -- More objections : betrayal from within? -- Other ideas : the search continues -- Extinction matters -- Epilogue : Can the megafauna live again?
Includes bibliographical references (pages 199-223) and index.
Keywords: Extinct animals; Extinction (Biology); Animals -- Effect of human beings on; Morphology (Animals); Body size